2020
DOI: 10.5194/amt-13-2413-2020
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of particle-size selectivity of optical low-cost particulate matter sensors

Abstract: Abstract. Low-cost particulate matter (PM) sensors have been under investigation as it has been hypothesized that the use of low-cost and easy-to-use sensors could allow cost-efficient extension of the currently sparse measurement coverage. While the majority of the existing literature highlights that low-cost sensors can indeed be a valuable addition to the list of commonly used measurement tools, it often reiterates that the risk of sensor misuse is still high and that the data obtained from the sensors are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 41 publications
6
104
0
2
Order By: Relevance
“…Newer methods, based on optical particle sensors (OPS), are nowadays increasingly more popular, particularly lowcost variants (Zheng et al, 2019;Mukherjee et al, 2019;Tanzer et al, 2019;Morawska et al, 2018). Their typical time resolution is between 1 s and 1 min, and because of their price and size, they can be used in networks to provide better spatial coverage (Martin et al, 2019;Li et al, 2019). Furthermore, they provide information about multiple mass fractions of particulate matter simultaneously, unlike the concentration of a single fraction in a gravimetric system or BAM.…”
Section: Introductionmentioning
confidence: 99%
“…Newer methods, based on optical particle sensors (OPS), are nowadays increasingly more popular, particularly lowcost variants (Zheng et al, 2019;Mukherjee et al, 2019;Tanzer et al, 2019;Morawska et al, 2018). Their typical time resolution is between 1 s and 1 min, and because of their price and size, they can be used in networks to provide better spatial coverage (Martin et al, 2019;Li et al, 2019). Furthermore, they provide information about multiple mass fractions of particulate matter simultaneously, unlike the concentration of a single fraction in a gravimetric system or BAM.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the data produced should be used with care, and data correction is often suggested due to the disagreement with reference devices [ 14 , 22 , 23 , 24 , 25 ]. Comparison to the reference aerosol spectrometer (Grimm 1.108) showed that low-cost sensors, including PMS5003 used in this study, showed different performance than declared by the manufactures and provided a proper response in a limited range of bins [ 26 ]. On the other hand, the PMS series sensor showed a higher measurement quality than the Alphasense OPC-N2 (the previous model of the one used in our study) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the Plantower PMS5003 can not accurately determine the PM 10 fraction. One possible explanation is provided by a laboratory test of PMS5003, where it was found that its size bin [2.5 µm-10 µm] is noisy and inaccurate (Kuula et al, 2020). Further investigation of this behavior would be useful.…”
Section: Strong Urban Pollutionmentioning
confidence: 99%
“…Laboratory tests and calibrations of OPS are performed under controlled conditions with known aerosols, such as polystyrene latex spheres (Walser et al, 2017;Bezantakos et al, 2018), continuously changing monodisperse, particles (Kuula et al, 2017(Kuula et al, , 2020 or multi-modal aerosols (Cai et al, 2019). Burning chamber is used in some investigations as well (Wang et al, 2015).…”
mentioning
confidence: 99%